Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Union Metal - Betty Rahayu; Aslichah Aslichah; Fian Nurul Hidayat (Peneliti.net, 2022)
This study aimed to determine and analyze the effect of work motivation and discipline on employee performance either simultaneously or partially. The type of research used in this study is a survey method, namely research in which data is collected from respondents using a questionnaire. The sample in the study was 40 respondents. Sources of data use primary and secondary data, namely literature and from the Internet. In comparison, the data analysis technique used in this study is a quantitative analysis using analysis through the SPSS 25 program. The results of the study based on multiple linear regression analysis with the F test (simultaneous) show that the variables of work motivation and work discipline have a simultaneous influence. The results of the t-test analysis can be concluded that the variables of work motivation and work discipline have a partial influence